A nuclear grade boron-10 acid purification process

After dissolving boron-10 acid in ultrapure water, and purifying using nanofiltration membrane and recrystallization technology, the problems of complex processes and low yields are solved, and the production of high-purity nuclear-grade boron-10 acid is achieved. Meets the quality requirements of nuclear power plants.

CN118221128BActive Publication Date: 2025-02-18SHANDONG CHENGWU YIXIN ENVIRONMENTAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410270205.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-11
Publication Date
2025-02-18
Estimated Expiration
2044-03-11

AI Technical Summary

Technical Problem

The existing boron-10 acid purification process is complex, has low yields, is not environmentally friendly, and it is difficult to meet the quality indicators of nuclear power plants.

Method used

The normal purity boron-10 acid was completely dissolved in ultrapure water of 95°C to 100°C, and the nanofiltration membrane was heat filtration and recrystallized to obtain high-purity nuclear-grade boron-10 acid.

Benefits of technology

The process is simplified, the yield is improved, the environmental burden is reduced, the impurity content is reduced, and the quality indicators for the use of nuclear power plants are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118221128B_ABST
    Figure CN118221128B_ABST
Patent Text Reader

Abstract

The present invention relates to a purification process of nuclear-grade boron-10 acid, which belongs to the technical field of physical purification, and comprises the following steps: 1) completely dissolving boron-10 acid of ordinary purity in 95-100°C ultrapure water; 2) hot filtering the boron-10 acid mother liquor through a nanofiltration membrane to obtain a crude filtrate; 3) the crude filtrate is cooled and crystallized to obtain a crude boron-10 acid, and the crude boron-10 acid is purified by recrystallization to obtain a high-purity nuclear-grade boron-10 acid. In the technical scheme of the present invention, a boron-10 acid solution of ordinary purity is hot filtered and recrystallized through a nanofiltration membrane to remove most of the cations, anions and water-insoluble substances in the boron-10 acid to reach the purity of nuclear-grade boron-10 acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of purification, and in particular, relates to a nuclear-grade boron-10 acid purification process. Background Art

[0002] There are two stable isotopes of natural boron, boron-10 and boron-11, with molar abundances of 19.78% and 80.22% respectively. The absorption cross section of boron-10 for thermal neutrons is 3837 bar, while the absorption cross section of natural abundance boron for thermal neutrons is close to 750 bar, while that of boron-11 is only 0.005 bar. Boric acid, i.e., boron-10 isotope, is a white powdery crystal or scaly shiny crystal. Boric acid is usually solid H3 10 It exists in the form of BO3. Benefiting from the powerful radiation protection and thermal neutron absorption functions of boric acid-10 and the continuous breakthrough of boric acid-10 process technology, boric acid-10 has been widely used in nuclear radiation shielding and neutron protection in the field of nuclear power generation.

[0003] In the field of nuclear power generation, boric acid-10 can not only be used directly in nuclear power plants as the preferred chemical compensation control agent to ensure that the neutron shielding function of the nuclear reactor cooling system is efficient and safe, thereby effectively improving the safety and flexibility of nuclear power plant operation, but also be used as the core raw material for nuclear reactor control rods to improve the level of nuclear reactor reaction intensity control. In addition, as a neutron shielding material, boric acid-10 can also be used in nuclear waste storage and transportation, effectively preventing nuclear proliferation and making nuclear waste treatment more efficient, safe and reliable.

[0004] The designed service life of a nuclear power plant is no less than 60 years, which places high demands on the quality indicators of boric acid-10, requiring that the content of individual anions and cations shall not be higher than 0.5ppm, and the content of water-insoluble matter shall not be higher than 20ppm. The existing quality indicators of boric acid-10 are difficult to meet the requirements for use in nuclear power plants, so it is necessary and imperative to study a nuclear-grade boric acid-10 purification process. Summary of the invention

[0005] The object of the present invention is to provide a nuclear grade boron-10 acid purification process.

[0006] The technical problem to be solved by the present invention is that the purification process of boric acid-10 in the prior art is relatively complicated.

[0007] The yield is low, it is not environmentally friendly, and the impurity content control indicators cannot meet the requirements for use in nuclear power plants.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] 1) Completely dissolve ordinary purity boric acid-10 in ultrapure water at 95°C to 100°C;

[0010] 2) hot filtering the boric acid 10 mother liquor through a nanofiltration membrane to obtain a crude filtrate;

[0011] 3) The crude filtrate is cooled and crystallized to obtain crude boron-10 acid, and the crude boron-10 acid is purified for a second time by recrystallization to obtain high-purity nuclear-grade boron-10 acid.

[0012] Furthermore, the dissolution process is as follows: ultrapure water is added to the dissolution kettle, heated to 95°C to 100°C, and ordinary purity boric acid 10 is added in a mass ratio of boric acid 10: ultrapure water = 20 to 30: 100. Stirring at a constant temperature until the boric acid 10 solid is completely dissolved, the stirring state is maintained, and the boric acid 10 mother liquor is hot filtered through a nanofiltration membrane to obtain a crude filtrate.

[0013] In some embodiments, the dissolving tank and the stirring device are made of 316L stainless steel, stainless steel lined with polytetrafluoroethylene, or stainless steel lined with enamel.

[0014] In some embodiments, the dissolving tank and the stirring device are made of stainless steel lined with polytetrafluoroethylene or stainless steel lined with enamel.

[0015] In some embodiments, the ultrapure water heating temperature is 95°C to 100°C.

[0016] In some embodiments, the ultrapure water heating temperature is 96°C to 98°C.

[0017] In some embodiments, the mass ratio of boric acid-10 to ultrapure water is 15-30:100.

[0018] In some embodiments, the mass ratio of boric acid-10 to ultrapure water is 25-30:100.

[0019] Furthermore, the nanofiltration membrane is prepared as follows:

[0020] A1. Soak the base filter membrane in ethanol solution and ultrapure water to remove pollutants, and dry it in a vacuum oven;

[0021] A2, dissolving a certain proportion of polyethyleneimine / phthalimide (0.5-1.5wt%) in ultrapure water, directing and pouring the resulting aqueous solution mixture onto the surface of the base filter membrane and keeping it for 1 minute; then, pouring out the excess aqueous solution and removing the residual solution with a rubber roller;

[0022] A3, dissolving 0.1wt% of trimesoyl chloride in n-heptane solvent as an organic phase, and soaking the base filter membrane obtained in step A2 in the trimesoyl chloride solution for 10 minutes, and placing it in an oven at 75°C for 10 minutes for further cross-linking. After the reaction is completed, rinse with ultrapure water to obtain.

[0023] The polymers on the surface of the nanofiltration membrane are as follows:

[0024]

[0025] Furthermore, the base filtration membrane is a ceramic ultrafiltration membrane, which is prepared by the following steps:

[0026] B1. The alumina ceramic membrane support was ultrasonically cleaned with ultrapure water, treated in 5% dilute hydrochloric acid for 3 hours after drying, and then ultrasonically cleaned with ultrapure water, dried in an oven at 90°C and set aside for use. Al2O3 powder was used as a raw material, the solid phase volume fraction of the powder was 45%, and a polymethyl methacrylate (PMMA) prepolymer liquid with a viscosity of 3000mPa·S was used as a premixed liquid. 0.4% PEG200 was added as a dispersant, and 0.5% TiO2 and 6% MgO were added as sintering aids to prepare a stable ceramic membrane transition layer slurry. The film was coated by a doctor blade method. After the coating was dried and solidified, it was placed in a muffle furnace and calcined at 1450°C for 1 hour to prepare a transition layer.

[0027] B2. Prepare a slurry consisting of nano-Al2O3 powder and PMMA prepolymer liquid, with the mass fraction of nano-Al2O3 powder in the slurry system being 5%, coat a separation layer on the surface of the transition layer, dry and solidify, sinter at 1450°C, and keep warm for 1 hour to prepare a separation layer, thereby obtaining a ceramic ultrafiltration membrane.

[0028] Furthermore, in step B1, the median diameter of the Al2O3 powder is 3.321 μm.

[0029] Furthermore, in step B2, the median diameter of the nano-alumina is 25.231 nm.

[0030] Furthermore, the preparation process of the alumina powder is as follows:

[0031] The concentration of 0.199g / mL anhydrous AlCl3 and 0.534g / mL NH4HCO4 solution, the volume ratio of the two reaction solutions is 1:1, by adjusting the pH value between 7 and 9.5, adding 0.2% of the total mass of the reaction system dispersant, the anhydrous AlCl3 solution is slowly dripped into the NH4HCO4 for reaction, and the dripping speed is controlled to be 3mL / min. After the reaction is complete, it is aged for 30min; the precursor obtained by the precipitation reaction is washed with ultrapure water 1 to 2 times to remove impurity ions in the precursor, after filtering the washing water, it is washed with anhydrous ethanol 1 to 2 times to remove moisture, prevent the formation of chemical bonds, and play a certain dispersing role to avoid the occurrence of hard agglomeration, and then filter it, the washed precursor is placed in an oven for drying and grinding, and then placed in a muffle furnace for calcination at 650°C to obtain alumina powder.

[0032] Furthermore, the preparation process of the alumina ceramic membrane support is as follows: after the support aggregate is evenly mixed with the solvent, binder, pore-forming agent, and sintering aid, the moisture in the slurry is removed, and after granulation, a green embryo is prepared by a dry pressing molding process. The operating pressure is 30MPa, and the pressure holding time is 60s. The green embryo is calcined at 1450°C for 1h to obtain the alumina ceramic membrane support.

[0033] Furthermore, the support aggregate is prepared by mixing a-Al2O3 powder with a median diameter of 3 μm and a-Al2O3 powder with a median diameter of 10 μm in a ratio of 1:1.

[0034] Furthermore, the crude filtrate is cooled and crystallized to obtain crude boron-10 acid, and the crude boron-10 acid is recrystallized, centrifugally filtered and dried to obtain high-purity nuclear-grade boron-10 acid.

[0035] In some embodiments, the cooling crystallization temperature is 5°C to 15°C.

[0036] In some embodiments, the cooling crystallization temperature is 5°C to 10°C

[0037] In some embodiments, the drying temperature is no greater than 70°C.

[0038] In some embodiments, the drying temperature is 50°C to 65°C.

[0039] Beneficial effects of the present invention:

[0040] (1) In the technical solution of the present invention, the hot mother liquor of boric acid 10 of ordinary purity is filtered through a ceramic nanofiltration membrane and recrystallized, which simplifies the process, reduces the loss of boric acid 10 in the process, improves the yield, reduces the environmental burden, greatly reduces the content of metal ions, non-metallic ions, heavy metal ions, inorganic anions and water-insoluble substances in boric acid 10, improves the purity of boric acid 10, and the impurity content index meets the requirements for use in nuclear power plants.

[0041] (2) In the technical solution of the present invention, phthalimide and polyethyleneimine are introduced on the surface of the ceramic ultrafiltration membrane through interfacial polymerization reaction to prepare a positively charged ceramic ultrafiltration membrane, thereby improving the retention effect of metal ions.

[0042] (3) In the technical solution of the present invention, the ceramic nanofiltration membrane has a narrow pore size distribution and strong mechanical, thermal and chemical stability. It can remove adsorbed anions and cations and water-insoluble substances under certain conditions and can be reused after regeneration. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Solubility curve of boric acid-10 in water DETAILED DESCRIPTION

[0044] The following will be combined with the embodiments of the present invention and the accompanying drawings to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Preparation Example 1

[0046] The preparation process of alumina powder is as follows:

[0047] The concentration of 0.199g / mL anhydrous AlCl3 and 0.534g / mL NH4HCO4 solution, the volume ratio of the two reaction solutions is 1:1, by adjusting the pH value between 7 and 9.5, adding 0.2% of the total mass of the reaction system dispersant, the anhydrous AlCl3 solution is slowly dripped into the NH4HCO4 for reaction, and the dripping speed is controlled to be 3mL / min. After the reaction is complete, it is aged for 30min; the precursor obtained by the precipitation reaction is washed with ultrapure water 1 to 2 times to remove impurity ions in the precursor, after filtering the washing water, it is washed with anhydrous ethanol 1 to 2 times, and then filtered, the washed precursor is placed in an oven for drying and grinding, and then placed in a muffle furnace and calcined at 650°C to obtain alumina powder.

[0048] Preparation Example 2

[0049] The preparation process of alumina ceramic membrane support is as follows:

[0050] The support aggregate is mixed evenly with a solvent (ultrapure water), a binder (0.06% polyvinyl alcohol), a pore-forming agent (6% soluble starch), and a sintering aid (0.5% MgO + 2% TiO2 + 1.5% MnO2 + 1.5% CuO), and the moisture in the slurry is removed. After granulation, a green embryo is prepared by a dry pressing process, with an operating pressure of 30 MPa and a holding time of 60 seconds. The green embryo is calcined at 1450°C for 1 hour to obtain an alumina ceramic membrane support;

[0051] The supporting aggregate is prepared by mixing a-Al2O3 powder with a median diameter of 3 μm and a-Al2O3 powder with a median diameter of 10 μm in a ratio of 1:1.

[0052] Preparation Example 3

[0053] The ceramic ultrafiltration membrane is prepared by the following steps:

[0054] B1. The alumina ceramic membrane support was ultrasonically cleaned with ultrapure water, treated in 5% dilute hydrochloric acid for 3 hours after drying, and then ultrasonically cleaned with ultrapure water, dried in an oven at 90°C and set aside for use. Al2O3 powder with a median diameter of 3.321 μm was used as a raw material, the solid phase volume fraction of the powder was 45%, and PMMA prepolymer liquid with a viscosity of 3000 mPa·S was used as a premixed liquid. 0.4% PEG200 was added as a dispersant, and 0.5% TiO2 and 6% MgO were added as sintering aids to prepare a stable ceramic membrane transition layer slurry, which was coated by a doctor blade method. After the coating was dried and solidified, it was placed in a muffle furnace and calcined at 1450°C for 1 hour to prepare a transition layer;

[0055] B2. Prepare a slurry consisting of nano-Al2O3 powder with a median diameter of 25.231nm and PMMA prepolymer liquid, with the mass fraction of nano-Al2O3 powder in the slurry system being 5%. Coat a separation layer on the surface of the transition layer, dry and solidify it, sinter it at 1450°C, and keep it warm for 1 hour to prepare a separation layer, thereby obtaining a ceramic ultrafiltration membrane.

[0056] Preparation Example 4

[0057] The nanofiltration membrane was prepared as follows:

[0058] A1. Soak the base filter membrane in ethanol solution and ultrapure water to remove pollutants, and dry it in a vacuum oven;

[0059] A2. Dissolve 0.5 wt% polyethyleneimine / phthalimide in ultrapure water, guide and pour the resulting aqueous solution mixture onto the surface of the base filter membrane and keep it for 1 minute; then, pour out the excess aqueous solution and remove the residual solution with a rubber roller.

[0060] A3, dissolving 0.1wt% of trimesoyl chloride in n-heptane solvent as an organic phase, and soaking the base filter membrane obtained in step A2 in the trimesoyl chloride solution for 10 minutes, and placing it in an oven at 75°C for 10 minutes for further cross-linking. After the reaction is completed, rinse with ultrapure water to obtain.

[0061] Preparation Example 5

[0062] The nanofiltration membrane was prepared as follows:

[0063] A1. Soak the base filter membrane in ethanol solution and ultrapure water to remove pollutants, and dry it in a vacuum oven;

[0064] A2. Dissolve 1 wt% polyethyleneimine / phthalimide in ultrapure water, guide and pour the resulting aqueous solution mixture onto the surface of the base filter membrane and keep it for 1 minute; then, pour out the excess aqueous solution and remove the residual solution with a rubber roller.

[0065] A3, dissolving 0.1wt% of trimesoyl chloride in n-heptane solvent as an organic phase, and soaking the base filter membrane obtained in step A2 in the trimesoyl chloride solution for 10 minutes, and placing it in an oven at 75°C for 10 minutes for further cross-linking. After the reaction is completed, rinse with ultrapure water to obtain.

[0066] Preparation Example 6

[0067] The nanofiltration membrane was prepared as follows:

[0068] A1. Soak the base filter membrane in ethanol solution and ultrapure water to remove pollutants, and dry it in a vacuum oven;

[0069] A2. Dissolve 1.5 wt% polyethyleneimine (Mn=70,000 g / mol) / phthalimide in ultrapure water, guide and pour the resulting aqueous solution mixture onto the surface of the base filter membrane and keep it for 1 minute; then, pour out the excess aqueous solution and remove the residual solution with a rubber roller.

[0070] A3, dissolving 0.1wt% of trimesoyl chloride in n-heptane solvent as an organic phase, and soaking the base filter membrane obtained in step A2 in the trimesoyl chloride solution for 10 minutes, and placing it in an oven at 75°C for 10 minutes for further cross-linking. After the reaction is completed, rinse with ultrapure water to obtain.

[0071] Example 1

[0072] A nuclear grade boron-10 acid purification process comprises the following steps:

[0073] 1) Add ultrapure water to the dissolving kettle, heat to 95° C., and add ordinary purity boric acid 10 according to the mass ratio of boric acid 10: ultrapure water = 20:100. Stir at 95° C. until the boric acid 10 solid is completely dissolved, keep stirring, and hot filter the boric acid 10 mother liquor through the nanofiltration membrane of Preparation Example 4 to obtain a crude filtrate.

[0074] 2) The crude filtrate is cooled to 5° C. by heat exchange with a low-temperature refrigerant for cooling and crystallization to obtain crude boric acid-10. The crude boric acid-10 is recrystallized, centrifugally filtered and dried at 60° C. and -0.1 MPa vacuum conditions to obtain a high-purity boric acid-10 product.

[0075] Example 2

[0076] A nuclear grade boron-10 acid purification process comprises the following steps:

[0077] 1) Add ultrapure water to the dissolving kettle, heat to 97° C., and add ordinary purity boric acid 10 according to the mass ratio of boric acid 10: ultrapure water = 25:100. Stir at 97° C. until the boric acid 10 solid is completely dissolved, keep stirring, and hot filter the boric acid 10 mother liquor through the nanofiltration membrane of Preparation Example 4 to obtain a crude filtrate.

[0078] 2) The crude filtrate is cooled to 10° C. by heat exchange with a low-temperature refrigerant for cooling and crystallization to obtain crude boric acid-10. The crude boric acid-10 is recrystallized, centrifugally filtered and dried at 65° C. and -0.1 MPa vacuum conditions to obtain a high-purity boric acid-10 product.

[0079] Example 3

[0080] A nuclear grade boron-10 acid purification process comprises the following steps:

[0081] 1) Add ultrapure water to the dissolving kettle, heat to 97° C., and add ordinary purity boric acid 10 according to the mass ratio of boric acid 10: ultrapure water = 25:100. Stir at 97° C. until the boric acid 10 solid is completely dissolved, keep stirring, and hot filter the boric acid 10 mother liquor through the nanofiltration membrane of Preparation Example 5 to obtain a crude filtrate.

[0082] 2) The crude filtrate is cooled to 10° C. by heat exchange with a low-temperature refrigerant for cooling and crystallization to obtain crude boric acid-10. The crude boric acid-10 is recrystallized, centrifugally filtered and dried at 65° C. and -0.1 MPa vacuum conditions to obtain a high-purity boric acid-10 product.

[0083] Example 4

[0084] A nuclear grade boron-10 acid purification process comprises the following steps:

[0085] 1) Add ultrapure water to the dissolving kettle, heat to 97° C., and add ordinary purity boric acid 10 according to the mass ratio of boric acid 10: ultrapure water = 25:100. Stir at 97° C. until the boric acid 10 solid is completely dissolved, keep stirring, and hot filter the boric acid 10 mother liquor through the nanofiltration membrane of Preparation Example 6 to obtain a crude filtrate.

[0086] 2) The crude filtrate is cooled to 10° C. by heat exchange with a low-temperature refrigerant for cooling and crystallization to obtain crude boric acid-10. The crude boric acid-10 is recrystallized, centrifugally filtered and dried at 65° C. and -0.1 MPa vacuum conditions to obtain a high-purity boric acid-10 product.

[0087] Comparative Example 1

[0088] The difference between this comparative example and Example 2 is that no nano-Al2O3 powder separation layer is added to the surface of the ceramic ultrafiltration membrane transition layer, and the remaining steps and raw materials are the same as those of Example 2.

[0089] Comparative Example 2

[0090] The difference between this comparative example and Example 2 is that the surface of the nanofiltration membrane is not modified by phthalimide and polyethyleneimine, and the remaining steps and raw materials are the same as those of Example 2.

[0091] Comparative Example 3

[0092] The difference between this comparative example and Example 2 is that the base filtration membrane adopts a polysulfone ultrafiltration membrane, and the remaining steps and raw materials are the same as those in Example 2.

[0093] Comparative Example 4

[0094] A conventional purification process for boric acid-10 comprises the following steps:

[0095] 1) Add ultrapure water to the dissolving kettle, heat to 97°C, and add ordinary purity boric acid 10 according to the mass ratio of boric acid 10: ultrapure water = 15:100. Stir at 97°C until the boric acid 10 solid is completely dissolved, keep stirring, cool the boric acid 10 mother liquor to 60°C, and perform hot filtration through a cation exchange resin column and an anion exchange resin column in turn to obtain a crude filtrate.

[0096] 2) The crude filtrate is cooled to 10° C. by heat exchange with a low-temperature refrigerant for cooling and crystallization to obtain crude boric acid-10. The crude boric acid-10 is recrystallized, centrifugally filtered, and dried at 65° C. and -0.1 MPa vacuum conditions to obtain a boric acid-10 product.

[0097] Comparative Example 5

[0098] A conventional purification process for boric acid-10 comprises the following steps:

[0099] 1) Add ultrapure water to the dissolving kettle, heat to 97°C, and add ordinary purity boric acid 10 according to the mass ratio of boric acid 10: ultrapure water = 25:100. Stir at 97°C until the boric acid 10 solid is completely dissolved, keep stirring, and hot filter the boric acid 10 mother liquor through a cation exchange resin column and an anion exchange resin column in turn to obtain a crude filtrate.

[0100] 2) The crude filtrate is cooled to 10° C. by heat exchange with a low-temperature refrigerant for cooling and crystallization to obtain crude boric acid-10. The crude boric acid-10 is recrystallized, centrifugally filtered, and dried at 65° C. and -0.1 MPa vacuum conditions to obtain a boric acid-10 product.

[0101] The boric acid prepared in Examples 1-4 and Comparative Examples 1-5 was tested according to the test standard of GB / T 538-2018, and the results are shown in Table 1 below:

[0102] Table 1 Boron-10 acid ion content, water-insoluble matter, water content and yield

[0103]

[0104]

[0105] As can be seen from Table 1 above, the ceramic nanofiltration membrane filtration method used in the present invention can significantly reduce the anion and cation content and water-insoluble matter content in boric acid-10, so that its impurity content indicators meet the use standards of nuclear power plants (the content of a single anion and cation shall not be higher than 0.5ppm, and the content of water-insoluble matter shall not be higher than 20ppm).

[0106] As can be seen from Table 1 above, the ceramic nanofiltration membrane filtration method used in the present invention has a high applicable temperature, the solubility of boric acid-10 is positively correlated with the temperature, the concentration of boric acid-10 mother liquor is high, and the adsorption of boric acid-10 anions by anion exchange resin can be avoided. The combination of the two effects can significantly improve the yield of boric acid-10.

[0107] It can be seen from Table 1 above that the surface modification using phthalimide and polyethyleneimine in the present invention can greatly increase the retention of metals and their salts by the nanofiltration membrane, and in combination with the effect of the ceramic-based membrane, can better retain metal ions.

[0108] As can be seen from Table 1 above, in the conventional purification process of boric acid-10, the temperature has a great influence on the efficacy of anion and cation exchange resins (the upper temperature limit of the cation exchange resin is 80°C, and the upper temperature limit of the anion exchange resin is 60°C. Too high liquid temperature will reduce the adsorption strength of the resin to ions and also affect the chemical stability of the resin). The solubility of boric acid-10 is positively correlated with temperature, and the conventional purification process affects the purification efficiency.

[0109] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A process for purifying nuclear grade boric acid-10, characterized in that: The process steps are: 1) Completely dissolve ordinary purity boric acid-10 in ultrapure water at 95℃~100℃; 2) hot filtration of the boric acid 10 mother liquor through a nanofiltration membrane to obtain a crude filtrate; 3) The crude filtrate is cooled and crystallized to obtain crude boron-10 acid, and the crude boron-10 acid is purified for a second time by recrystallization to obtain high-purity nuclear-grade boron-10 acid; Steps 1) and 2) are specifically as follows: adding ultrapure water to a dissolving kettle, heating to 95°C to 100°C, adding boric acid of ordinary purity in a mass ratio of boric acid to ultrapure water = 15 to 30:100; stirring at a constant temperature until the boric acid solid is completely dissolved, maintaining the stirring state, and hot filtering the boric acid mother liquor through a nanofiltration membrane to obtain a crude filtrate; The preparation of the nanofiltration membrane is as follows: A1. Soak the base filter membrane in ethanol solution and ultrapure water to remove pollutants, and dry it in a vacuum oven; A2, dissolving polyethyleneimine and phthalimide in ultrapure water, directing and pouring the resulting aqueous solution mixture onto the surface of the base filter membrane and maintaining it for 1 minute; then, pouring out the excess aqueous solution and removing the residual solution with a rubber roller; A3, dissolving trimesoyl chloride in n-heptane solvent as an organic phase, and soaking the base filter membrane obtained in step A2 in the trimesoyl chloride solution for 10 minutes, and placing it in an oven at 75° C. for 10 minutes for further cross-linking. After the reaction is completed, washing with ultrapure water to obtain; The base filter membrane is a ceramic ultrafiltration membrane, which is prepared by the following steps: B1. The alumina ceramic membrane support was ultrasonically cleaned with ultrapure water, treated in 5% dilute hydrochloric acid for 3 hours after drying, and then ultrasonically cleaned with ultrapure water, dried in an oven at 90°C for use, Al2O3 powder was used as raw material, the solid phase volume fraction of the powder was 45%, and PMMA prepolymer liquid with a viscosity of 3000mPa·S was used as a premixed liquid, 0.4% PEG200 was added as a dispersant, 0.5% TiO2 and 6% MgO were added as sintering aids, a stable ceramic membrane transition layer slurry was prepared, and the film was coated by a doctor blade method. After the coating was dried and solidified, it was placed in a muffle furnace and calcined and kept warm at 1450°C for 1 hour to prepare a transition layer; B2. Prepare a slurry consisting of nano-Al2O3 powder and PMMA prepolymer liquid, with the mass fraction of nano-Al2O3 powder in the slurry system being 5%, coat a separation layer on the surface of the transition layer, dry and solidify, sinter at 1450°C, and keep warm for 1 hour to prepare a separation layer, thereby obtaining a ceramic ultrafiltration membrane.

2. The purification process of nuclear grade boric acid-10 according to claim 1, characterized in that: The crude filtrate is cooled and crystallized to obtain crude boron-10 acid. The crude boron-10 acid is recrystallized, centrifugally filtered and dried to obtain high-purity nuclear grade boron-10 acid.

3. The purification process of nuclear grade boric acid-10 according to claim 1, characterized in that: The resistivity of ultrapure water is above 18.2MΩ·cm (25℃).

4. The purification process of nuclear grade boric acid-10 according to claim 1, characterized in that: The cooling crystallization temperature is 5°C to 15°C, the drying temperature is not higher than 70°C, and the vacuum degree is -0.1MPa.

5. The purification process of nuclear grade boric acid-10 according to claim 1, characterized in that: In step B1, the median diameter of the Al2O3 powder is 3.321 μm; In step B2, the median diameter of nano-alumina is 25.231 nm; The preparation process of the alumina powder is as follows: The concentration of 0.199g / mL anhydrous AlCl3 and 0.534g / mL NH4HCO3 solution, the volume ratio of the two reaction solutions is 1:1, by adjusting the pH value between 7 and 9.5, adding 0.2% of the total mass of the reaction system dispersant, the anhydrous AlCl3 solution is slowly dripped into the NH4HCO3 for reaction, and the dripping speed is controlled to be 3mL / min. After the reaction is complete, it is aged for 30min; the precursor obtained by the precipitation reaction is washed with ultrapure water 1 to 2 times to remove impurity ions in the precursor, after filtering the washing water, it is washed with anhydrous ethanol 1 to 2 times, and then filtered, the washed precursor is placed in an oven for drying and grinding, and then placed in a muffle furnace and calcined at 650°C to obtain alumina powder.

6. The process for purifying nuclear grade boric acid-10 according to claim 5, characterized in that: The preparation process of the alumina ceramic membrane support is as follows: after the support aggregate is uniformly mixed with the solvent, the binder, the pore-forming agent, and the sintering aid, the moisture in the slurry is removed, and after granulation, a green embryo is prepared by a dry pressing process, the operating pressure is 30MPa, the pressure holding time is 60s, and the green embryo is calcined at 1450°C for 1h to obtain the alumina ceramic membrane support; The support aggregate is prepared by mixing a-Al2O3 powder with a median diameter of 3 μm and a-Al2O3 powder with a median diameter of 10 μm in a ratio of 1:1.

Citation Information

Patent Citations

  • Preparation method for nuclear-grade high-purity boric acid

    CN103787349A

  • Positively charged composite nanofiltration membrane as well as preparation method and application thereof

    CN111330447A

  • Novel high-flux positively charged nanofiltration membrane and preparation method thereof

    CN113262644A